Wakaf Produktif dalam Ekonomi Islam : Analisis Pemikiran Muhammad Abdul Mannan dan Implementasinya pada Pembangunan Berkelanjutan - Arinal Nasir; Hanafi Nur Zain; Rafi Kenny Akhdan; Lina Marlina (Journal of Islamic Economics and Finance, 2025)
Productive waqf is an innovation in the Islamic economic system aimed at professionally managing waqf assets to provide sustainable economic benefits for society. This study analyzes Muhammad Abdul Mannan’s thoughts on productive waqf and its relevance in supporting sustainable development. Using a qualitative approach through literature review, this research explores Mannan’s ideas, including the concepts of cash waqf and share waqf, which allow waqf assets to be developed to generate social and economic benefits. The findings indicate that productive waqf serves not only as a means of worship but also as an economic instrument that can reduce poverty, create jobs, and strengthen the financial independence of the Muslim community. Furthermore, the implementation of productive waqf has significant potential in supporting the achievement of Sustainable Development Goals (SDGs) by funding social, educational, health, and economic empowerment programs. Despite its great potential, the application of productive waqf in Indonesia faces challenges such as a lack of public understanding, insufficient regulatory support, and limited human resources. This study is expected to contribute to optimizing the management of productive waqf to support sustainable development in Indonesia.